Green Infrastructure in the Urban Environment: A Systematic Quantitative Review - Parker, Jacqueline; Zingoni de Baro, Maria Elena (MDPI AG, 2019)
Increased levels of greenhouse gases released into the atmosphere, a legacy of the industrial revolution, population growth pressures, and consumerist lifestyle choices, are the main contributors to human-induced climate change. Climate change is commensurate of warming temperatures, reductions in rainfall, increased frequency of extreme weather events, and contributions toward declining public health trends. Green Infrastructure (GI) presents diverse opportunities to mediate adverse effects, while simultaneously delivering human health, well-being, environmental, economic, and social benefits to contemporary urban dwellers. To identify the current state of GI knowledge, a systematic quantitative literature review of peer-reviewed articles (n = 171) was undertaken using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) method. Temporal publication trends, geographical and geological information of research efforts, as well as research focus areas were recorded and reported against each article. The findings of this review confirm the research area to be in a state of development in most parts of the world, with the vast majority of the research emerging from the United States, Australia, and the United Kingdom. Cooler climates produced the majority of research, which were found largely to be of a traditional research article format. The GI research area is firmly dominated by foci comprising planning and policy, environmental and ecological, and social content, although modest attempts have also appeared in health and wellbeing, economic, and quality/performance of green infrastructure areas. Knowledge gaps identified by this review as requiring attention for research growth were identified as: (i) the ambiguity of terminology and the limited broad understanding of GI, and (ii) the absence of research produced in the continents of Asia and South America, as well as in regions with warmer climates, which are arguably equally valuable research locations as cooler climate bands.